Present status and challenges of fodder production in controlled environments: a review - Ahamed, Md Shamim; Sultan, Muhammad; Shamshiri, Redmond R.; Rahman, Md Mostafizar; Aleem, Muhammad; Balasundram, Siva K. (Elsevier BV, 2023)
Hydroponic fodder production in controlled environment (CE) settings have gained more focus in recent years due to the shortage of agricultural land for food production and the adverse effect of climate changes. However, the operation costs and dry matter issues are the major concerns for the sustainability of fodder production in the CE. This study provides a comprehensive literature review on techniques and control strategies for indoor environments and watering that are currently used and could be adopted in the future to achieve the economic and environmental sustainability of controlled environment fodder production (CEFP). The literature indicates fodder production in the modular system is becoming popular in developed countries, and low-tech systems like greenhouse are more prevalent in developing countries. The optimum temperature and RH range between 16- 27◦C and 70-80 to get efficient biomass yield; however, minimal research has been conducted to optimize the indoor temperature and relative humidity (RH) for efficient and higher efficiency fodder production. Besides, the water-saving techniques and optimal lighting spectrum need to be studied extensively. Automating and monitoring in CEFP system could reduce operating costs and improve quality and yield. Overall, this industry might have great potential for livestock production. Still, more strong research needs to be conducted to answer nutritional concerns and reduce the capital and operating costs for CEFP.